STRESS AND STRAIN STATE OF REPAIRING SECTION OF PIPELINE - V. V. Nikolaev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Reliability of continuous operation of pipelines is an actual problem. For this reason should be developed an effective warning system of the main pipelines‘  failures and accidents not only in design and operation but also in selected repair. Changing of linear, unloaded by bending position leads to the change of stress and strain state of pipelines. And besides this, the stress and strain state should be determined and controlled in the process of carrying out the repair works. The article presents mathematical model of pipeline’s section straining in viscoelastic setting taking into account soils creep and high-speed stress state of pipeline with the purpose of stresses evaluation and load-supporting capacity of repairing section of pipeline, depending on time.  Stress and strain state analysis of pipeline includes longitudinal and circular stresses calculation  with  account of axis-asymmetrical straining and  was  fulfilled  on  the base of momentless theory of shells. To prove the consistency of data there were compared the calcu- lation results and the solution results by analytical methods for different cases (long pipeline’s section strain only under influence of cross-axis action; long pipeline’s section strain under in- fluence of longitudinal stress; long pipeline’s section strain; which is on the elastic foundation, under influence of cross-axis action). Comparison results shows that the calculation error is not more than 3 %.Analysis of stress-strain state change of pipeline’s section was carried out with development  of  this  model,  which  indicates  the  enlargement  of  span  deflection  in  comparison with problem’s solution in elastic approach. It is also proved, that for consistent assessment of pipeline maintenance conditions, it is necessary to consider the areolas of rheological processes of soils. On the base of complex analysis of pipelines there were determined stresses and time-deflection relation for two types of soils with different rheological properties.